2015
DOI: 10.1002/app.41917
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of carbon fiber sizing and its influence on the interphase region of composites

Abstract: What might happen with the interphase region of composite if the sizing agent cannot afford the attack of processing temperature and firstly reacted before its combination with the resin, is rarely reported. On the basis of this, herein, effects of sizing reaction on the interphase region of composite were investigated, as well as on the carbon fiber surface properties. It showed that the interfacial shear strength of carbon fiber/epoxy composite was improved after the sizing reaction. The interphase modulus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…This demonstrates that the pronounced modification effects have occurred on the surface of CFs after sizing. The nitrogen on unsized fibers may derive from the incomplete carbonization of PAN‐based precursor . However, the nitrogen is not found on sized CFs, indicating that no nitric groups are present in sizing and this is consistent with the above FTIR analyses.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…This demonstrates that the pronounced modification effects have occurred on the surface of CFs after sizing. The nitrogen on unsized fibers may derive from the incomplete carbonization of PAN‐based precursor . However, the nitrogen is not found on sized CFs, indicating that no nitric groups are present in sizing and this is consistent with the above FTIR analyses.…”
Section: Resultssupporting
confidence: 84%
“…Meanwhile, the sizing performs as a uniform layer on the surface of CFs. It can absorb some stress, scatter external stress as well as change the propagation paths of crack when suffering external force . In this way, the sizing layer on the defective parts plays a role of inhibiting internal stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All fibers surfaces looked smooth and it suggested that there was no significant difference in the roughness. It may be correlated that the weight percentage of sizing agents was really low and the sizing layer was thin .…”
Section: Resultsmentioning
confidence: 99%
“…32,33 The strong bands at 1631 cm 21 were attributed to the C@O stretching vibrations on the surface of CF. 34 The strong bands at 1261 and 802 cm 21 were attributed to the CAOAC stretching vibrations in epoxy group, 35,36 and the strong bands at 1095 and 1022 cm 21 were assigned to the CAO stretching vibrations. [37][38][39] These indicated that there was epoxy sizing agent on CF.…”
Section: Resultsmentioning
confidence: 99%